Relationship of Knowledge and Attitude of Pregnant Women to Antenatal Care Examinations During the Covid 19 Pandemic - Cyntia Theresia Lumintang; Filia Veronica Tiwatu (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Pregnancy is a process that will be experienced by every woman. The Maternal Mortality Rate (MMR) in Indonesia is still quite high, one of the efforts made to reduce the MMR in Indonesia is the Antenatal Care (ANC) examination program. The Covid-19 pandemic has changed the status of life around the world suddenly, causing a very large psychological burden, especially for pregnant women. ANC services during the current Corona Virus Disease 2019 (Covid-19) pandemic will certainly be greatly affected and at risk of experiencing a decline. pregnancy care visits. This study aims to determine the relationship between the level of knowledge, attitudes and behavior of pregnant women towards antenatal care examinations during the COVID-19 pandemic in the Public Health Center of Modoinding. This type of research is an analytic survey with a cross sectional approach, the sampling technique is using purposive sampling, the number of samples is 50 respondents. The research data was obtained through a questionnaire of knowledge, attitudes and behavior of pregnant women about antenatal care and then analyzed using the Chi Square test with Cl = 95% and α = 0.05. The results of statistical tests showed that there was a relationship between the behavior of ANC examination visits and the knowledge and behavior of pregnant women, while related to attitudes, there was no relationship between the behavior of ANC examination visits and attitudes. In conclusion, there is a relationship between knowledge and behavior of pregnant women in ANC examination, and there is no relationship between behavior of ANC examination visits and attitudes of pregnant women in ANC examination in the Public Health Center of Modoinding.